Intangible flow theory in economics : human participation in economic and societal production - Cardao-Pito, Tiago (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2021)
"The dominant economic explanations of the twentieth century are not comprehensive enough to describe the complexity of economy and society, and their reliance on the biosphere. Intangible Flow Theory in Economics: Human Participation in Economic and Societal Production outlines a new theory which challenges both economics and the relativism conveyed in social constructivism, poststructuralism and postmodernism. To mainstream economics and Marxism, monetary flows transform us humans into commodities. To this new theory, flows of economic elements as physical goods or money are consummated by intangible flows that cannot yet be precisely appraised at an actual or approximate value, for instance workflows, service flows, information flows or communicational flows. The theory suggests a systematic alternative to refute the human commodity framework and interrelated conjectures (e.g. human capital, human resources, human assets). Furthermore, it exhibits that economic and societal production is fully integrated on the biosphere. Conversely, contemporary relativism argues for end of theory development, suspension of evidence and entrenchment of knowledge validity among local systems (named as paradigms, epistemes, research programs, truth regimes, or other terms). Thus, relativism tacitly supports dominant theories as the human commodity framework because it preventively sabotages the creation of new theoretical explanations. Disputing relativist theses, intangible flow theory demonstrates that innovative theoretical explanations remain possible. This book is of significant interest to students and scholars of political economy, economic sociology, organization, economics, and social theory. Tiago Cardao-Pito is an Assistant Professor at ISEG, Universidade de Lisboa (University of Lisbon), Portugal"--
OCLC-licensed vendor bibliographic record.
Keywords: Economics -- Sociological aspects; Human capital; BUSINESS & ECONOMICS / Economic History; BUSINESS & ECONOMICS / Economics / General